STRATEGI PENGEMBANGAN KERJASAMA SISTER CITY KOTA SEMARANG, INDONESIA – BRISBANE, AUSTRALIA - Damayanti, Nadia (Universitas Negeri Semarang, 2018)
The aim of this research is to know whether there are internal and external factors of Semarang City Government and to look for the most sutable strategy that could be perform in Sister City Semarang ? Brisbane. The primary data were gathered by using questionnaire and interviewing experts who understand about Sister City. The secondary data were taken from books, scientific journal, and earlier research. The data retrieval methods are interview, observation, documentation, library studies, and questionnaire. The analytic tools that being used in this research is SWOT analysis and descriptive analysis. There are external and internal factors that could influence from the strength perspective is education and science technology scope of Semarang. From weakness perspective is spoken-written English of Semarang Government?s staffs. From opportunity perspective is increasing development chances of human resources and more cooperation such as student exchange, cooperation between both countries. From threat perspective is the loose relationship between both Government of Indonesia and Australia The citizens of Semarang City also need to take action in the matter of Sister City. By taking action, there will be some kind of continuity of Sister City of Semarang City and Brisbane City, of course still with Semarang City Government intervention. Tujuan penelitian yaitu untuk melihat faktor eksternal dan faktor internal Pemerintah Kota Semarang serta strategi yang tepat untuk kerjasama Sister City Kota Semarang ? Kota Brisbane. Data primer diambil dengan wawancara dan kuesioner kepada ahli yang menangani bidang kerjasama Sister City. Data sekunder diambil dari buku, penelitian terdahulu, dan jurnal. Metode pengambilan data yaitu wawancara, observasi, dokumentasi, studi kepustakaan, dan angket. Analisis penelitian menggunakan analisis SWOT dan analisis Deskriptif. Berdasarkan hasil penelitian bahwa faktor eksternal dan faktor internal yang mempengaruhi yaitu dari sisi kekuatan pada faktor internal merupakan dari bidang pendidikan dan IPTEK Kota Semarang. Sisi kelemahan yaitu kemampuan staf berbahasa Inggris Pemerintah Kota Semarang. Sisi Peluang dari faktor eksternal yaitu peningkatan SDM dan  kesempatan berupa kerjasama, dan pertukaran pelajar. Sisi ancaman yaitu hubungan Pemerintah Indonesia dengan Pemerintah Australia yang sempat renggang. Saran yaitu  masyarakat dan pengusaha sebaiknya ikut terlibat dalam kerjasama Sister City. Adanya keterlibatan masyarakat dalam kerjasama Sister City dapat menciptakan keberlangsungan kerjasama dan tentunya dalam pengawasan pemerintah